Environmental Impact Assessment Under the Protocol on Environment Protection to the Antarctic Treaty and Australian Legislation - Fallon, L; Kriwoken, L (2005)
The objective of this paper is to assess how the requirements for EIA have been put in place by the Australian Commonwealth government (hereafter referred to as the Commonwealth government) under national legislation. This paper draws on research conducted in 2002 and 2003. Qualitative data in the form of semistructured key informant interviews were conducted with senior Australian Antarctic administrators to elicit their views on the introduction of new Australian environmental legislation and its impact, and key similarities and differences, on existing Australian Antarctic legislation and associated regulations. The paper begins with an examination of the three tiers of EIA as outlined in the Madrid Protocol and the relevant Australian legislation. The paper then provides an analysis of the EIA process in the following eight themes: planning provisions; resources of concern; environmental documentation; categorical exclusions; thresholds; cumulative impacts; public involvement; and dispute resolution, compliance and enforcement. Tentative conclusions are made with respect to the roles and responsibilities of both the Antarctic Treaty (Environment Protection) Act 1980 (Cth) (AT(EP) Act) and the Environment Protection and Biodiversity Conservation Act 1999 (Cth) (EPBC Act) in enhancing Australia's capacity to protect the Antarctic environment. Discussion is limited to the Antarctic Treaty Area and therefore does not include the Australian sub-Antarctic islands.